If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 5m + -8m + 2 = 0 Reorder the terms: 2 + m + 5m + -8m = 0 Combine like terms: m + 5m = 6m 2 + 6m + -8m = 0 Combine like terms: 6m + -8m = -2m 2 + -2m = 0 Solving 2 + -2m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2m = 0 + -2 -2m = 0 + -2 Combine like terms: 0 + -2 = -2 -2m = -2 Divide each side by '-2'. m = 1 Simplifying m = 1
| 4b-5b=5 | | 3(c+2)=24 | | m-5m-4m-5= | | 5s-7+4-2s+7z= | | x^4-18x^2+45=0 | | 39k+12=2k-11 | | m-m+4m+1= | | a=500(1+.06/2)*2 | | 3/8x-1/3+6 | | 3x-7=3(x+6) | | a=500(1+.06/2)2 | | C=8x+75 | | 9/3*(24/8) | | 16x-8-2=20 | | 9/3(24/8) | | 225-725x= | | 27/45 | | -35m-15=69 | | z^4+5iz^2+8=0 | | -4m-15=51 | | -28m-10=54 | | 7(3x/5)=11-(x/9) | | e^4x+3e^2x-18=0 | | 40x+.25y=50 | | -14m-12=79 | | cos^2(x)-sin^2(x)= | | 27y+12= | | 6x^6-9x^5-27x^4= | | 200.00+0.05s=75+0.10s | | 4x^4-4+x^3-x^2=0 | | 3x+10=5x-30 | | 24x^2+18x+5=0 |